Why aging induces deflation and secular stagnation - R. Anton Braun; Daisuke Ikeda (Federal Reserve Bank of Atlanta, 2022)
We provide a quantitative theory of deflation and secular stagnation. In our lifecycle framework, an aging population puts persistent downward pressure on the price level, real interest rates, and output. A novel feature of our theory is that it also recognizes the reactions of government policy. The central bank responds to falling prices by reducing its policy nominal interest rate, and the fiscal authority responds by allowing the public debt-gross domestic product ratio to rise.
Keywords: E52; E62; G51; D15; 330; monetary policy; lifecycle; portfolio choice; secular stagnation; nominal government debt; aging; Tobin effect; fiscal policy; deflation